From COMECON to CARICOM : towards the integration of the Republic of Cuba into the Caribbean Community - Wedderburn, Carlos Moore ed. (Caricom Secretariat GeorgetownGY, 1998)
Focuses on aspects of the Cuban integration into the Caribbean Community such as, structural and institutional concerns; political and ethno-cultural problems; and, U.S./Cuba/Caribbean security issues. Sees Cuba's integration into Caricom as an opportunity to erect a regional strategic bloc. Makes recommendations.